Digitisation of public procurement as a factor of economic security and regional development in the Kyrgyz Republic - G. Shirdakova; Zh. Arnakunova; D. Temirov; A. Ulan uulu; A. Kuvatbekov (Науковий вісник Мукачівського державного університету. Серія Економіка)
The purpose of this study was to assess the impact of digitalisation of public procurement on economic resilience, transparency, and regional development in the Kyrgyz Republic. Legislative and regulatory acts, as well as the practical features of the Kyrgyz Republic’s digitalisation of public procurement between 2019 and 2024, served as the basis for the study. It was determined that the implementation of such systems contributed to a significant reduction in costs, improved access to data and reduced corruption. According to the results of the study, the total volume of public procurement in 2019 exceeded KGS 63 billion, which indicated the scale of public spending managed through the electronic platform. By the end of 2020, more than 27,590 suppliers and 4,072 purchasing organisations had registered on the platform, showing a high level of engagement in the system. In 2019, a total of 77,477 tenders were conducted through the e-procurement portal, emphasising the system’s wide use and scale. As a result of the Manual’s assistance in monitoring 1,632 requests during the first quarter of 2023, 510 tenders were cancelled, 547 tenders with breaches were eliminated, and 13 tenders with notable violations were identified. Over 12% of Kyrgyzstan’s gross domestic product (GDP) was derived from governmental procurement in 2023. Around USD 1.4 billion was spent on public procurement annually, with Kyrgyzstan’s GDP projected to reach USD 11.7 billion in 2023. The practical significance of this study lies in its potential to guide further improvements in the digitalisation of public procurement in the Kyrgyz Republic, with a focus on enhancing efficiency, transparency, and inclusivity, ultimately supporting regional economic development and reducing corruption risks